1979
DOI: 10.1038/bjc.1979.169
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation by the mitotic inhibitor NY 3170 of human cells in vitro

Abstract: Summary.-Inactivation of NHIK 3025 cells by the mitotic inhibitor NY 3170 (1-propargyl-5-chloropyrimidin-2-one) was measured as loss of colony-forming ability. NY 3170 at a concentration of 0-15 mM allowed no formation of colonies after 12 days of continuous exposure to the drug.Metaphase arrest after treatment with NY 3170 was reversible if the drug was removed immediately after the onset of the arrest. When the cells were kept in mitosis by the presence of NY 3170, inactivation was complete after 8h incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…This property is somewhat different from that earlier reported for NY 3170 (5). In that case about 50~ of the cells were able to form colonies even after 4 hr mitotic arrest in the presence of a concentration (0.2 mM) giving nearly complete metaphase arrest.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This property is somewhat different from that earlier reported for NY 3170 (5). In that case about 50~ of the cells were able to form colonies even after 4 hr mitotic arrest in the presence of a concentration (0.2 mM) giving nearly complete metaphase arrest.…”
Section: Discussioncontrasting
confidence: 90%
“…One of these, 1-propargyl-5-chloropyrimidin-2-one (NY 3170), * Fellow of the Norwegian Cancer Society (Landsforeningen mot Kreft). has been studied closely in vitro both on cells grown in monolayer (4)(5)(6) and in spheroids (7). This compound was shown to induce a metaphase arresting effect in the concentration range 0.05 to 0.4 mM on cells grown in monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Results with the metahalone NY 3170 are quite different. Reports have shown that mitotic arrest caused by NY 3170 is induced if, and only if, this drug is present during mitosis (5,6). During continuous treatment with NY 4137 (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…I-Propargyl-5-chloropyrimidin-2-one (NY 3170) is a mitotic inhibitor which causes reversible metaphase inhibition in cultured cells (Wibe & Oftebro, 1979). A sufficient, but necessary prerequisite for metaphase inhibition is that the drug be present during mitosis (Wibe et al, 1979).…”
mentioning
confidence: 99%
“…A sufficient, but necessary prerequisite for metaphase inhibition is that the drug be present during mitosis (Wibe et al, 1979). The parent compound 5-chloropyrimidin-2-one (NY 3000) also induces metaphase arrest in cultured cells (Wibe et al, 1978).…”
mentioning
confidence: 99%